Проблемные вопросы расчета контактных напряжений зубьев силовых передач - Шевченко, Р. И. (НТУ "ХПИ", 2005)
The operation is dedicated to problems by bound with state ment and solution of a task of definition of contact stresses in teeth of gears in conditions of active corrode.
Keywords: зацепление Новикова; формула Герца; напряженно-деформированное состояние; площадка контакта